THE INFLUENCE OF BUILDING LAND AND ELECTRICITY INFRASTRUCTURE TAXES ON ECONOMIC GROWTH IN INDONESIA - Muhammad Isan; Reza Juanda; Muammar Khaddafi (RADJA PUBLIKA, 2023)
This study aims to analyze the effect of land and building taxes and electricity infrastructure on economic growth in Indonesia. This research uses secondary data from 2010-2020. Data were analyzed using multiple linear regression (Ordinary Least Squares). Based on the results of the study, it shows that the variable Land and Building Tax has an effect on Economic Growth, while the Electricity Infrastructure variable has no effect on Economic Growth. Simultaneously the variables of Land and Building Tax and Electricity Infrastructure affect Economic Growth. The coefficient of determination R2 in this study is 0.462970, meaning that the effect of the variable Land and Building Tax and Electricity Infrastructure on Economic Growth is 0.462970 or 46.29%. While the remaining 0.53703 (53.703%) is influenced by other variables outside this study.